2016
DOI: 10.1371/journal.pone.0166000
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of the Pathogenicity-Related Gene VdPR1 in the Vascular Wilt Fungus Verticillium dahliae

Abstract: Verticillium dahliae Kleb., the causal agent of vascular wilt, can seriously diminish the yield and quality of many crops, including cotton. The pathogenic mechanism to cotton is complicated and unclear now. To screen pathogencity related genes and identify their function is the reliable way to explain the mechanism. In this study, we obtained a low-pathogenicity mutant vdpr1 from a T-DNA insertional library of the highly virulent isolate of V. dahliae Vd080, isolated from cotton. The tagged gene was named pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…As our understanding of the pathogenicity of V. dahliae increases, it appears that a variety of genes are required for virulence towards host plants, including protein kinases (Rauyaree et al ., ; Tian et al ., ; Tzima et al ., ), TFs (Luo et al ., ; Santhanam et al ., ; Sarmiento‐Villamil et al ., ; Tran et al ., ; Xiong et al ., ), effectors (de Jonge et al ., ; Liu et al ., ; Santhanam et al ., ), enzymes involved in plant cell wall degradation (Chen et al ., ; Liu et al ., ; Maruthachalam et al ., ) and other functional genes (Gao et al ., ; Klimes and Dobinson, ; Li et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). In this study, we identified a new pathogenicity and virulence‐related gene encoding a Fungal_trans domain‐containing TF (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…As our understanding of the pathogenicity of V. dahliae increases, it appears that a variety of genes are required for virulence towards host plants, including protein kinases (Rauyaree et al ., ; Tian et al ., ; Tzima et al ., ), TFs (Luo et al ., ; Santhanam et al ., ; Sarmiento‐Villamil et al ., ; Tran et al ., ; Xiong et al ., ), effectors (de Jonge et al ., ; Liu et al ., ; Santhanam et al ., ), enzymes involved in plant cell wall degradation (Chen et al ., ; Liu et al ., ; Maruthachalam et al ., ) and other functional genes (Gao et al ., ; Klimes and Dobinson, ; Li et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). In this study, we identified a new pathogenicity and virulence‐related gene encoding a Fungal_trans domain‐containing TF (Figs and ).…”
Section: Discussionmentioning
confidence: 97%
“…Several V. dahliae pathogenicity‐related genes have been identified (Chen et al ., ; de Jonge et al ., ; Liu et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhou et al ., ). In addition, several pathogenicity‐related genes have been identified using T‐DNA insertion mutagenesis (Gao et al ., ; Li et al ., ; Luo et al ., ; Maruthachalam et al ., ; Santhanam et al ., ; Zhang DD et al ., ; Zhang YL et al ., ). Collectively, these studies indicate that the processes associated with pathogenicity are complex, and that a variety of V. dahliae gene products are required for host infection.…”
Section: Introductionmentioning
confidence: 97%
“…Verticillium wilt is caused by the systemic colonization of V. dahliae in plant vascular tissues, and plant roots usually serve as the first battleground between V. dahliae and plant host [ 36 ]. The colonization of V. dahliae on cotton roots directly affects the incidence of cotton Verticillium wilt [ 37 ]. Next, the xylem is the second battlefield of V. dahliae and plant host that compete for nutrition [ 38 ].…”
Section: Discussionmentioning
confidence: 99%
“…The experiment was performed five times. Spore yields at 24, 48, and 72 hpt were estimated with a hemocytometer [ 37 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fungal strain and cotton variety V. dahliae Vd080 (Zhang et al 2016) which was used in this study was kept on potato dextrose agar (PDA) medium. The mycelia of V. dahliae were obtained from growing the strain in potato dextrose broth (PDB) medium at 28°C, 160 rpm for 12 days.…”
Section: Methodsmentioning
confidence: 99%